The clinical outcome of pembrolizumab for patients with recurrent or metastatic squamous cell carcinoma of the head and neck: a single center, real world study in China - Fan, Zongyu; Hui, Rongrong; Ju, Houyu; Wu, Yunteng; Ma, Xuhui; Song, Hao; Liu, Yang; Rui, Mengyu; Geng, Xinrong; Zhao, Minqi; Xin, Yingye; Wei, Dongliang; et al. (Frontiers in Oncology, 2024)
Background: The KEYNOTE-048 and KEYNOTE-040 study have demonstrated the efficacy of pembrolizumab in recurrent or metastatic squamous cell carcinoma of the head and neck（R/M HNSCC）,we conducted this real-world study to investigate the efficacy of pembrolizumab in patients with R/M HNSCC. Methods: This is a single-center retrospective study conducted in the Shanghai Ninth People’s Hospital Affiliated to Shanghai Jiao Tong University School of Medicine (Shanghai, China).Between December 2020 and December 2022, a total of 77 patients with R/M HNSCC were included into analysis.The primary endpoint of the study was overall survival（OS）, and the secondary endpoints were progression-free survival（PFS）, overall response rate（ORR）and toxicity.Efficacy was assessed according to RECIST version 1.1.SPSS 27.0 and GraphPad Prism 8.0 software were utilized to perform the statistical analysis. Results: By the cut-off date (February 28, 2023), the median OS,PFS and ORR were 15.97 months,8.53 months and 48.9% in patients treated with the pembrolizumab regimen in the first line therapy. Among these patients, 17 patients received pembrolizumab with cetuximab,and 18 received pembrolizumab with chemotherapy.We observed no significant differences between two groups neither in median OS (13.9 vs 19.4 months, P=0.3582) nor PFS (unreached vs 8.233 months, P= 0.2807). In the ≥2nd line therapy (n=30), the median OS, PFS and ORR were 5.7 months, 2.58 months and 20% respectively. Combined positive score (CPS) was eligible from 54 patients. For first line therapy, the median OS and PFS were 14.6 and 8.53 months in patients with CPS ≥1, and median OS and PFS were 14.6 and 12.33 months in patients with CPS ≥20. The immune-related adverse events (irAEs) were occurred in the 31 patients (31/77, 40.26%), and the most common potential irAEs were hypothyroidism (25.97%), and pneumonitis (7.79%).